Rancang Bangun dan Pengaruh Susunan Pisau Setengah Helix pada Mesin Pencacah Limbah Sayur - Nugraha, Nurcahya; Pramana, Tunggul (Politeknik Caltex Riau, 2023)
Vegetable waste is leftover vegetables that are withered and rotting. Usually, vegetable waste becomes garbage that ends up in a landfill. These wastes still contain high water content and have the potential to be used as animal feed or compost. However, there are obstacles to its utilization. The main obstacle in utilizing vegetable waste to be used as animal feed is the size of the vegetable waste, which tends to be too large so that it cannot be used directly as animal feed. Therefore, we need technology that can simplify the enumeration process. A vegetable waste chopping machine is one of the right counter technologies for utilizing vegetable waste. The vegetable waste chopping machine is designed to use a horizontal shaft and is driven by an AC electric motor with a power of 1 hp. Pulley and belt mechanisms are used to reduce rotation and transmit power from the motor to the chopping blade. This chopping machine uses a half-helix blade arrangement and a parallel arrangement. Tests were carried out on this machine to determine the advantages of selecting the half helix blade arrangement pattern compared to the parallel blade arrangement pattern and the chopping capacity possessed by the machine. In this study, an experiment was carried out using a rotational speed of 1800 rpm. The chopping machine with the half helix blade arrangement has a chopping capacity of 231.4 kg/hour, more significant than the parallel blade arrangement. Keywords: chopping machine, vegetable waste, helical blade